A comparative analysis with selected jurisdictions of structural challenges facing the South African office of the tax ombud - Mothiba, Boitumelo Charity (Rhodes University, Faculty of Commerce, Department of Accounting, 2020)
The Office of the Tax Ombud is critical in the protection of South African taxpayers' rights. The office has only been in existence for a little over five years and to ensure that it fulfils the purpose for which it was established, it must be properly structured. This includes that it ought to be independent from any external influence and manipulation. Any such external influence on the Tax Ombud creates the risk that the general public will lose confidence in the Tax Ombud as an independent recourse. The study, therefore, is designed to review the structure relating to the independence and powers of the South African Tax Ombud. The study assesses and evaluates the legislative safeguards of the structure of the Tax Ombud office in order to determine whether the legislative framework (the Tax Administration Act) safeguarding the Office of the Tax Ombud is adequate to ensure its independence and also to ensure a strengthened structure, without interference in the decision-making process of the office. To achieve this, a comparative analysis was made with selected foreign institutions of Tax Ombudsmen, or equivalent institutions, in order to draw from the best international practice. The study found that the structure of the Office of the Tax Ombud is relatively weak and does not fully provide the legislative powers to protect taxpayers from the well-resourced South African Revenue Service. The study also revealed that most of the institutional features in the structure of the South African Tax Ombud were found to be in line with standard international practice. The study has made recommendations aimed at strengthening the structure of the South African Tax Ombud by suggesting reforms in the legislative framework of the Tax Ombud.
Keywords: South Africa. Office of the Tax Ombud; Tax administration and procdure -- South Africa; Taxpayer advocates -- South Africa